(untitled) (World Economics and Finance Bulletin, 2024)
In the digital economy, modern technologies and innovative approaches are becoming increasingly important in attracting financial resources and ensuring their sustainability. This study analyzes the experience of European, American and Japanese banks, shows the share of attracting resources through digital channels and their specific features. Based on the experience of foreign banks, practical recommendations have been developed for the Uzbek banking system to create innovative products, develop digital platforms, strengthen cybersecurity and improve legislation. This study covers strategic approaches that will contribute to the sustainable development of banks in the digital economy.